Analysis Of Water Quality By Chemical And Biological Parameters In Gampong Gunung Samarinda, Babahrot District, Southwest Aceh District - Radha Al Asri; Khairil Khairil; Supriatno Supriatno; Samingan Samingan; Wiwit Artika (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2022)
A dug well is one of the wells that provide clean water by only digging the ground until it gets a layer of water with a certain depth consisting of the well edge, the inner well, the outer well, the well floor, the wastewater and equipped with bucket, coils or pump. This study aims to analyze the quality of community dug wells in Gampong Gunung Samarinda, Babahrot District, Southwest Aceh Regency based on chemical and biological parameters as well as the suitability of well water for consumption by the community of Gampong Gunung Samarinda, Babahrot District, Southwest Aceh Regency. The object of this research is dug well water. The parameters of this research are chemical and biological parameters. Analyze data with laboratory analysis and compare analysis results with water quality standards. The results of this research shows that the sample of water on well II residents of Gunung Samarinda village is feasible, based on the laboratory test each of the chemical parameters and biological parameters do not exceeds the standard of clean water quality. The water of well samples I and II can be said unfeasible based on the results of the analysis of biological parameters showing the content of E. Coli bacteria and Coliform is too high when compared to water quality standards.Keywords: well water, chemical parameter, biological parameterSumur galian adalah salah satu sumur penyedian air bersih dengan hanya menggali tanah sampai mendapat lapisan air dengan kedalaman tertentu yang terdiri dari bibir sumur, dinding sumur, lantai sumur, salinan air limbah dan dilengkapi dengan timbah dengan gulungan atau pompa. Penelitian ini bertujuan menganalisis kualitas sumur galian masyarakat di Gampong Gunung Samarinda Kecamatan Babahrot Kabupaten Aceh Barat Daya berdasarkan parameter kimia dan biologi serta kelayakan air sumur untuk dikonsumsi. Objek pada penelitian ini adalah air sumur galian. Parameter dari penelitian ini adalah parameter kimia dan biologi. Analisis data dengan analisis laboratorium dan membandingkan hasil analisis dengan standar mutu air. Hasil penelitianAir sumur warga Gampong Gunung Samarinda pada masing-masing pengukuran besi, kesadahan dan pH tidak melebihi dari standar baku mutu dan pengujian E.coli dan Coliform menunjukkan bahwa adanya bakteri E. coli dan Coliform pada sumur I dan III. Air sumur I dan III belum layak dikonsumsi sebagai kebutuhan domestik. Kata Kunci:Jamur Merang, Produktivitas, Media Tanam